Petani Muslim Kuningan Dalam Pusaran Konflik Kelas (Jurnal Penelitian, 2016)
This study examines Marx’s theory which states that in the process of capitalization, small land farmers will be displaced by large land farmers. This study employs a qualitative approach using the Participatory Action Research (PAR) method. Through participatory field observation techniques, the study also conducted in-depth interviews with farmers. Data were analyzed using an inductive approach. The findings indicate that Marx’s theory does not occur in Aman Malar. The decline in agriculture is caused by decreasing soil fertility, high production costs, land conversion, and climate change. Meanwhile, the survival strategies of small land farmers include practicing intercropping patterns, taking additional jobs, and managing household finances.
Keywords: agriculture, Karl Marx, class fight, capital